The Influence of the Pregnant Friend Application on Pregnant Women's Attitudes and Knowledge about Danger Signs of Pregnancy at RSIA Masyita - Syarif, Sutrani; Eryanti Kusniyanto, Rahayu; Darman, Amriani (Universitas Andalas, 2024)
Background: Every pregnancy carries the risk of mild or severe complications that cause death, morbidity, disability in the mother or baby. Attitudes and knowledge about the danger signs of pregnancy are very important to prevent unwanted complications during pregnancy. Efforts to increase knowledge and attitudes about the danger signs of pregnancy are very necessary. The pregnant friend application is a health application for pregnant women as a means of communicating between pregnant women and midwives to gain knowledge and convey complaints about pregnancy directly. Objective: to determine the effect of using the